PENGARUH PENGGUNAAN METODE PEMBELAJARAN JIBRIL TERHADAP KEMAMPUAN MEMBACA AL-QUR’AN SISWA - Siti Maulida Ulva; Ahmad Izza Muttaqin; Muhammad Endy Fadlullah; Anis Fauzi (MUMTAZ : Jurnal Pendidikan Agama Islam, 2023)
One of the factors of low ability to read Al-Quran on students in Junior high school Darussyafa'ah setail road, which is the teacher of the less skillfully apply a wide variety of methods to teach reading the Qur'an and the limitations of the school facilities and infrastructure that support the learning. To address these problems, the researchers are interested to apply the method of Gabriel in the increased ability of learning to read Al-Quran students with tartil and based on the science of tajweed. As in this study the researcher used Quantitative research, the researcher used the experimental method with quantitative approach. The sampling technique in this research using probability sampling or the sample is saturated. Data collection techniques in this study using the test, questionnaire, observation, Interview, documentation. While the data analysis by using normality test, homogeneity test, and t test test. Based on the analysis of the data to the test instrument test using validity and reliability. Of 5 about test declared invalid because of the results of r count is greater r table and had significant at <0.05. As for the reliability test is declared reliable because the cronbach alpha>0.6 a. Data analysis techniques using normality test, homogeneity test, and hypothesis test. The results of the normality test showed normal distribution of data because of significant value in the data value of the Pretest of 0,821>0,05. Homogeneity test shows shows the data are homogeneous because of the significant value of 0,532> 0,05. For T-test assessment of Pretest values obtained the ability to read Al-Quran by 3.5414 as for the value of posttest obtained by 4.0931. sig tailed 0,00<0,5. While the value of the correlation 0,103. So, it can be stated that the hypothesis is Ha accepted and Ho is rejected. Learning with the method of Gabriel to make students able to read the Qur'an properly and correctly.